2019
DOI: 10.1002/aenm.201803323
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Effects of Electrolyte Composition on the Performance and Stability of FeF2 Conversion‐Type Cathodes

Abstract: As an alternative to commercial Ni-and Co-based intercalation-type cathode materials, conversion-type metal fluoride (MF x ) cathodes are attracting more interest due to their promisses to increase cell-level energy density when coupled with lithium (Li) or silicon (Si)-based anodes. Among metal fluorides, iron fluorides (FeF 2 and FeF 3 ) are regarded as some of the most promising candidates due to their high capacity, moderately high potential and very low cost of Fe. In this study, we systematically investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
76
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(77 citation statements)
references
References 53 publications
1
76
0
Order By: Relevance
“…This stability is remarkable, even compared to the best electrolyte systems used in the literature, and stands in stark contrast to the rapidly increasing charge transfer resistance observed in the LP30 electrolyte. 24 In LP30 the charge transfer resistance fluctuates significantly between discharge and charge (Figure 2C). This is possibly related to the repetitive formation and partial dissolution of the SEI layer as corroborated by x-ray photoelectron spectroscopy (XPS).…”
Section: Electrochemical Performance In Ionic Liquid Electrolytesmentioning
confidence: 99%
See 1 more Smart Citation
“…This stability is remarkable, even compared to the best electrolyte systems used in the literature, and stands in stark contrast to the rapidly increasing charge transfer resistance observed in the LP30 electrolyte. 24 In LP30 the charge transfer resistance fluctuates significantly between discharge and charge (Figure 2C). This is possibly related to the repetitive formation and partial dissolution of the SEI layer as corroborated by x-ray photoelectron spectroscopy (XPS).…”
Section: Electrochemical Performance In Ionic Liquid Electrolytesmentioning
confidence: 99%
“…Huang et al showed that electrolyte selection could greatly affect the performance of FeF 2 electrodes. 24 In this work, 1 molal lithium bis(fluorosulfonylimide) (LiFSI) dissolved in the N-methyl-N-propyl pyrrolidinium FSI (Pyr 1,3 FSI) ionic liquid is presented as a superior electrolyte for the cycling of transition metal fluorides. The ionic liquid electrolyte precludes major failure mechanisms, preserves the nanorod morphology during cycling, and obviates the use of "strongly coupled" carbon frameworks.…”
mentioning
confidence: 99%
“…Noticeably, a slightly larger discharge capacity is observed in the first 10 cycles and then decreases. Irreversible changes likely occurred in the electrode at the early stage [ 33 , 34 ]. Furthermore, the as-assembled AIB has the power to light-up a commercial light-emitting diode (LED) lasting more than one hour ( Figure 6 h), confirming its promising practical applications for energy storage.…”
Section: Resultsmentioning
confidence: 99%
“…To address these problems, great efforts have been made focusing on the construction of nanostructured FeF 2 . For example, Zhang et al reported FeF 2 /carbon composite nanoparticles with a size of 50-100 nm that showed a capacity of 183 mA h g À1 at 60 mA g À1 [34], while Huang et al realized a capacity of 300 mA h g À1 at 140 mA g À1 by fabricating nanostructured FeF 2 of the sub 50 nm size [35]. Therefore, desirable electrochemical performance is expected to be achieved for FeF 2 materials through rational design and modification [28,36].…”
Section: Introductionmentioning
confidence: 99%